#TITLE_ALTERNATIVE# - SULAKSANA (NIM 22299005), ALEX
The general solution of pressure transient behaviour in fractal reservoir had been developed by Chang and Yortsos (1990). The solution was applied in analysis of interference test for infinite acting reservoir ( Salis, 1993) and it was also developed to include skin and wellbore storage ( Suabdi, 1995). The thesis is a step forward in fractal reservoir transient pressure study to analyse the effect of no-flow reservoir boundary especially for rectangular geometry. The method of images of well and superposition was used to represent the behaviour of pressure transient in bounded reservoir with no-flow boundary. The thesis generates set of logarithmic type-curve by grouping involved parameters into dimensionless form of pressure and time, PDF and tDA. Result of research validates by comparing with conventional non-fractal analysis method and it show that calculation result is close. The fractal dimension, which is represent reservoir heterogeneity, could be determined by type-curve matching procedures.